PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT, DENGAN KEGIATAN PROMOTIF DAN PREVENTIF DI SDN PEKAUMAN 2 MARTAPURA - Ulfah, Rasuna; Habibah, Siti Sab’atul; Kisworo Utami , Naning; Amperawati, Metty; Bunga Nurwati; Isnawati; Sri Nuryati; Danan; Anderi Fansurna; Meggy Wulandari Kai (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Dental caries is a disease experienced by almost 90% of children. The results of the 2018 Basic Health Research show an increase of around 40% in the rate of dental and oral health problems in South Kalimantan compared to the 2013 Riskesdas. Where the rate of dental and oral health problems in South Kalimantan in 2013 was 36.1%, increasing to 59.60% in 2018. This activity aims to increase dental and oral health knowledge and tooth brushing skills, improve dental and oral hygiene, reduce the rate of dental caries. The targets of this community service are students at SDN Pekauman 2 Martapura. The implementation of community service activities consists of several stages, namely: Preparation stage, implementation stage and evaluation stage. At the implementation stage, dental health education and mass toothbrush assistance were carried out. The results obtained increased knowledge about dental health from medium to high criteria.